2015
DOI: 10.1111/dote.12352
|View full text |Cite
|
Sign up to set email alerts
|

Relief of dysphagia during neoadjuvant treatment for cancer of the esophagus or gastroesophageal junction

Abstract: Dysphagia is the main symptom of cancer of the esophagus and gastroesophageal junction and causing nutritional problems and weight loss, often counteracted by insertion of self-expandable metal stents or nutrition via an enteral route. Clinical observations indicate that neoadjuvant therapy may effectively and promptly alleviate dysphagia, making such nutrition supportive interventions redundant before surgical resection. The objective of the current study was to carefully study the effects of induction neoadj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
4
19
1
1
Order By: Relevance
“…Reports of clinically significant improvement in dysphagia with neoadjuvant treatment identified the feasibility of preserving nutrition without EA [13,14,33]. Sunde and colleagues [14] demonstrated that significant relief could be observed with the first treatment of a platinum-based therapy in combination with 5fluorouracil and radiotherapy.…”
Section: Commentmentioning
confidence: 99%
See 4 more Smart Citations
“…Reports of clinically significant improvement in dysphagia with neoadjuvant treatment identified the feasibility of preserving nutrition without EA [13,14,33]. Sunde and colleagues [14] demonstrated that significant relief could be observed with the first treatment of a platinum-based therapy in combination with 5fluorouracil and radiotherapy.…”
Section: Commentmentioning
confidence: 99%
“…Reports of clinically significant improvement in dysphagia with neoadjuvant treatment identified the feasibility of preserving nutrition without EA [13,14,33]. Sunde and colleagues [14] demonstrated that significant relief could be observed with the first treatment of a platinum-based therapy in combination with 5fluorouracil and radiotherapy. Similar results were achieved by Cools-Lartigue and colleagues [13] in Toronto, with taxotere, cisplatin, and 5-fluorouracil (TCF), epirubicin, cisplatin, and 5-fluorouracil (ECF), or docetaxel, oxaliplatin, leucovorin, and 5-fluorouracil (FLOT) demonstrating improvement of dysphagia after the first cycle.…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations